STUDY OF DNA POLYMORPHISM OF THE CASTOR NEW LINES BASED ON RAPD MARKERS - Martin Vivodík (Journal of Microbiology, Biotechnology and Food Sciences, 2015)
The systematic evaluation of the molecular diversity encompassed in castor inbreds or parental lines offers an efficient means of exploiting the heterosis in castor as well as for management of biodiversity. Seventeen castor genotypes were assessed for genetic variability using Random Amplified Polymorphic DNA (RAPD) markers. Thirteen polymorphic RAPD primers amplified 102 DNA fragments, with an average of 7.85 fragments per primer. Number of amplified fragments ranged from 3 (OPE-07) to 13 (SIGMA-D-01), with the size of amplicons ranging from 100 to 1200 bp. The polymorphic information content (PIC) value ranged from 0.450 (OPE-07) to 0.892 (SIGMA-D-01) with an average of 0.771 and diversity index (DI) value ranged from 0.551 (OPE-07) to 0.894 (SIGMA-D-01) with an average of 0.787. The dendrogram based on hierarchical cluster analysis using UPGMA algorithm was prepared and analyzed genotypes were grouped into two main clusters and only two genotypes (RM-5 and RM-23) could not be distinguished.